Anti-inflammatory effects of interleukin-35 in acquired aplastic anemia. Issue 2 (December 2015) - Yu, Wei; Ge, Meili; Lu, Shihong; Shi, Jun; Li, Xingxin; Zhang, Jizhou; Wang, Min; Huang, Jinbo; Shao, Yingqi; Huang, Zhendong; Zhang, Jing; Nie, Neng; et al.
Highlights Plasma IL-35 levels were decreased in AA patients compared to healthy controls. Decreased IL-35 was closely correlated with disease severity of AA. IL-35 modulated the secretion of pro- and anti-inflammatory cytokines of AA. IL-35 regulated the differentiation of T cell subsets of AA.